Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.energyfuels.1c00613
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of CH4 Sorption onto a Shale Surface in the Presence of Cationic Surfactant

Abstract: A substantial amount of water used for fracking shale formations is trapped by capillary and interfacial forces. Such trapped water is detrimental to gas production because of its potential to obstruct gas’s desorption and, subsequently, its flow path. Surfactants are proposed to alleviate the problem; however, further insight is required to understand the underlying mechanism. In this study, a cationic surfactant, namely, cetyltrimethylammonium bromide (CTAB), and a clay-rich Marcellus shale are used to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…These results quantitatively agree with the limited literature data, which reported that shale samples became more water-wet after treatment with surfactant. Such behavior was linked to the ability of surfactants to manipulate the surface charge distribution in shales. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results quantitatively agree with the limited literature data, which reported that shale samples became more water-wet after treatment with surfactant. Such behavior was linked to the ability of surfactants to manipulate the surface charge distribution in shales. , …”
Section: Resultsmentioning
confidence: 99%
“…The effect of pressure and temperature on γ water/CH 4 remains similar even after adding CTAB. Some previous studies reported that surfactants reduced γ water/CH 4 at the water/CH 4 interface, ,, although these measurements were conducted either at one pressure point only or at low pressure and temperature conditions. Shales are commonly produced through hydraulic fracturing, where a significant proportion of fracturing fluid gets retained within the shale matrix and hinders the flow of adsorbed CH 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before performing fluid any surface analysis, organic matter in both samples were quantified by determine the total organic carbon (TOC). Pervious studies reported that TOC has significant influence on rock wettability [2,[10][11][12][13]. The contact angle measurements were then conducted, and the findings were documented as average contact angles.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, an isotherm model describes adsorption equilibrium, providing useful information on pore structure and capacity (Shen et al 2018a, b). Many studies have focused on methane adsorption isotherms in shale in recent years (Abdulelah 2018;Abdulelah et al 2021;Al-Mutarreb et al 2018;Chen et al 2019a, b;Meng et al 2020;Pang et al 2021;Rexer et al 2020). However, little research has been done on water vapor adsorption on shale rocks and the feasibility of isotherm models.…”
Section: Introductionmentioning
confidence: 99%